Managing complex projects and systems: a literature synthesis. Issue 1 (1st January 2020) - Ireland, Vernon; Statsenko, Larissa
ABSTRACT: This paper provides a comprehensive synthesis of the seminal literature in complex systems to identify a group of key complex systems parameters and models relevant to both systems engineering and construction project management. The key research question addressed is whether the traditional practice of engineering, particularly as applied to project management and systems engineering projects, would benefit from recognising the large body of work of complex adaptive systems. A conceptual framework, which applies to both complex construction projects and systems engineering projects is presented to assist your system engineers and project managers in dealing with project complexity. Adaptivity is required in complex projects and this responsibility needs to be at the enterprise level of programs and portfolios. Complex adaptive systems models such as Ashby's law of requisite variety, fractals and Power Laws, emergence, self-organisation and dynamic systems could benefit project based enterprises and system engineers. A group of complex systems tools, which are often neglected, such as mindfulness, preoccupation with failure, normalising deviance and humility are highlighted. A group of non-functional requirements for systems engineering projects is also proposed.